Catalysing cleaner production systems: benchmarking with the COVID‑19 lockdowns in South Africa - Magidi, J.; Nhamo, L.; Kurwakumire, E.; Gumindoga, W.; Mpandeli, S.; Liphadzi, S.; Mabhaudhi, Tafadzwanashe (CRC Press, 2024)
Industrial and vehicular emissions are among the major contributors to greenhouse gas (GHG) atmospheric concentration, causing ozone depletion, climate change, and health risks. Reducing air pollution to permissible levels fosters human and environmental health through reduced radiation, stabilised temperatures, and improved air quality. This chapter quantifies the spatio-temporal atmospheric pollution in South Africa using remotely sensed satellite data acquired between April 2019 and April 2020, just before and during the coronavirus disease 2019 (COVID-19) pandemic lockdown. Remotely sensed data are essential for quantifying and monitoring air quality over time by assessing the change in pollution indicators such as fine particulate matter (PM2.5) and nitrogen dioxide (NO2) content. An analysis of results reveals that NO2 levels in South Africa reduced by 20.5% during the COVID-19 lockdown period compared to normal economic activity. The findings were used to develop a framework to guide policy and support decision-making to formulate coherent strategies for reducing pollution and alignment towards a low-carbon economy. Developing controlling and monitoring systems that capture episodic pollution events and enhance cleaner production mechanisms is critical for ensuring low carbon emissions and reducing environmental and human health risks. Although most NO2 emissions are generated in urban environments, the effects are felt far beyond, with detrimental effects on the environment and human health.